2011
DOI: 10.1159/000328846
|View full text |Cite
|
Sign up to set email alerts
|

Genetics in Health Care: An Overview of Current and Emerging Models

Abstract: Background: With advances in genetic and genomic medicine, the optimal integration of genetic services into the health care system remains of major concern in many countries. Objectives: To review the current organisation of genetic services, mostly in Europe, North America and Australia, explore emerging service delivery models, and probe challenges inherent in the transition process. Methods: We conducted a literature review of genetics in clinical practice: testing, diagnosis, counselling, and treatment. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 133 publications
(102 reference statements)
1
106
0
6
Order By: Relevance
“…The first analysis of findings assessed the models of genetic service delivery in the VHA and found that a traditional model (as defined by Battista et al 39 ) of multidisciplinary clinics led by geneticists or coordinated services between geneticists and other providers was most prevalent, although there was variability in the organization of these services, with consults available on site, at another VA facility, via tele-genetics (video-/teleconferencing), or at non-VA facilities. This analysis also found non-genetics providers had integrated genetics into their practices, though there was considerable variability in the degree of integration by specialty.…”
Section: National Organizational Studiesmentioning
confidence: 99%
“…The first analysis of findings assessed the models of genetic service delivery in the VHA and found that a traditional model (as defined by Battista et al 39 ) of multidisciplinary clinics led by geneticists or coordinated services between geneticists and other providers was most prevalent, although there was variability in the organization of these services, with consults available on site, at another VA facility, via tele-genetics (video-/teleconferencing), or at non-VA facilities. This analysis also found non-genetics providers had integrated genetics into their practices, though there was considerable variability in the degree of integration by specialty.…”
Section: National Organizational Studiesmentioning
confidence: 99%
“…3 The lack of medical geneticists has been recognized as a serious problem Objective: To characterize the delivery of genetic consultative services for adults, we examined the prevalence and organizational determinants of genetic consult availability and the organization of these services in the Veterans Health Administration.…”
Section: 11mentioning
confidence: 99%
“…This may reflect differences in health-care systems, including regulations governing genetic and genomic testing, health professional genetics education and training, and access to genetic health care and other health-care resources. 15 Therefore these external and organizational factors should be considered when planning the implementation of reporting secondary findings from exome or genome sequencing.…”
Section: Discussionmentioning
confidence: 99%